Enhancing sustainability in Indonesian SMEs through green HRM and supply chains - Eko Nur Fuad; Mohammad Yunies Edward; Moch Aminnudin; Muhammad Syahrul Rhomadhon (Problems and Perspectives in Management)
This study aims to evaluate how green HRM enhances sustainable performance in Indonesian SMEs by integrating green supply chain management and fostering pro-environmental behavior. By analyzing data from 645 SMEs across various industries, this paper explores the mediating effects of green supply chain management and pro-environmental behavior. The findings demonstrate that while green HRM has a direct negative impact on sustainable performance, its integration with green supply chain management and pro-environmental behavior significantly enhances sustainability outcomes. Additionally, green supply chain management and pro-environmental behavior mediate the relationship between green HRM and sustainable performance, indicating that green HRM indirectly fosters sustainability through these pathways. The study also shows that pro-environmental behavior moderates the effects of green HRM and green supply chain management on sustainable performance, strengthening both relationships. These results suggest that while green HRM alone may not directly improve sustainable performance, its integration with green supply chain management and pro-environmental behavior significantly enhances sustainability outcomes for SMEs. This study underscores the importance of fostering pro-environmental behavior and incorporating green supply chain practices within green HRM frameworks. It provides valuable contributions to the literature on sustainable business practices and offers practical guidance for SMEs to improve their sustainability performance.